Anda di halaman 1dari 16

lim

xc f(x) = L

x c f (x) L x c f (x) L

f (x) L x c

f (x) L x c f (x) L x c x c f (x) L

A R c R

A V δ (c) := (c δ, c + δ) A

c

(c δ, c + δ) A \ {c}

=

,

δ > 0.

A A A A A

A A

c A A (a n ) A a n = c n N lim(a n ) = c

c

1

|a n c| <

1

n N δ :=

1

1

1

n V n (c) = (cn , c+ n ) a n AV n a n = c

n 1 lim(a n ) = c

(a n ) A a n = c lim(a n ) = c c A lim(a n ) = c δ > 0 K

|a n c| < δ n K a K A, a K = c

a K V δ A V δ \ {c} =

c A

A

A = {−1} ∪ {x R : 0 x < 1} ∪ {2}.

A

x [0, 1] δ > 0 (x

δ,

x + δ) A \ {x} = x [0, 1] A

x

= 1

A δ 1 > 0 (1 δ 1 , 1 + δ 1 ) A = {−1}

(1 δ 1 , 1 + δ 1 ) A \ {−1} = x = 1 A x = 2 A

[0, 1]

∅ x = − 1 A x = 2 A [0 , 1] 1 ∈ /

1 / A 1 A 2 A 2 A [0, 1) A A

N

Q R

A = n : n N 0 A

A R f : A −→ R c A L f c

1

L = lim

xc f (x)

> 0 δ > 0

0 < |x c| < δ → |f (x) L| < .

δ δ( ) δ L f L c f (x) L x c f (x) L x c δ

diberikan V (L ) L + L |f(x)-L |< L - terdapat V (c) c+
diberikan V (L )
L +
L
|f(x)-L |<
L -
terdapat
V (c)
c+
c
c+

f (x) L x c

0 < |x c| < δ |f (x) L| < x c f (c) A A x = c

x = c

A R f

f c > 0 δ > 0

|x c| < δ → |f (x) f (c)| < .

A c A

: A −→ R c A

c A c A

f c f (c) c f (c) c

A R f : A −→ R c A c A

f c

lim xc f(x) = f(c)

E 1 := {x A : 0 < |x c| < δ},

E 2 := {x A : |x c| < δ}.

E 2

x E 1 x E 2 x = c x E 2

→ |f(x) f(c)| <

E 1

f c x E 2

diberikan V (f(c)) f(c)+ f(c) |f(x)-f(c)|< f(c)- terdapat V (c) c+ c c+
diberikan V (f(c))
f(c)+
f(c)
|f(x)-f(c)|<
f(c)-
terdapat
V (c)
c+
c
c+

f c

L = f (c) x = c |f (x) f (c)| = |f (c) f (c)| = 0 < lim xc f (x) = f (c) lim xc f (x) = f (c) x E 1 → |f (x) f (c)| < E 2 E 1 x E 2 → |f (x) f (c)| < f c

f R f (x) = b x R c R lim xc b = b f c

> 0 δ := 1

0 < |x c| < δ → |f(x) L| = |b b| = 0 < .

lim xc f (x) = f (c) c R f c.

δ 1 p q q

c R lim xc x = c f (x) := x c

> 0 δ :=

0 < |x c| < δ → |f(x) L| = |x c| < δ = .

lim xc x = c lim xc f (x) = f (c) c

f c

f (x) = x 2 , x R f R

c R

|f(x) f(c)| = |x 2 c 2 | = |x + c||x c|.

|x c| |x + c| |x c| < 1,

||x| − |c|| ≤ |x c| < 1 → −1 < |x| − |c| ≤ 1 → |x| ≤ |c| + 1.

|x + c|

|x + c| ≤ |x| + |c| ≤ 2|c| + 1.

|f (x) f (c)| = |x + c||x c| < (2|c| + 1) |x c|.

()

|x c| <

2|c| + 1 .

(∗∗)

|x c| < 1 |x c| <

2|c|+1

δ = δ( ) := min 1,

2|c| + 1 .

0 < |x c| < δ |f (x) f (c)| < lim xc f (x) = f (c) f c

c c f (c) c

f (x) = x 2 1 , x

= 0 1 f (1)

x1

x1 f (x) = lim

lim

x1

x 2 1

x 1

= lim

x1 (x + 1) = 2.

R

f(x) = x 2 1

x1

2

x

x = 0.

= 0

f : A −→ R c A

lim xc f(x) = L

= c

(x n ) A c x n n N (f (x n )) L

> 0 lim xc f (x) = L

δ > 0 0 < |x c| < δ |f (x) L| <

lim(x n ) = c x n

K N |x n c| < δ n K x n

0 < |x n c| < δ |f (x n ) L| < n K (f (x n )) L

= c

= c δ > 0

lim xc f (x)

= L

0

|f(x) x δ | ≥ 0 δ > 0 δ := n N (x n ) 0 < |x n c| <

|f (x n ) L| ≥ 0 n N (f (x n ))

L (x n ) A x n

L

δ

> 0

n 1 x n A

> 0 δ

> 0 x δ

A

0

<

|x x δ |

1

n

<

= c (f (x n ))

lim xc f (x)

= L (x n ) A x n

c lim (f (x n ))

= L

=

c (x n )

lim xc f (x) (x n ) A x n = c (x n ) c f (x n )

lim xc f (x) (x n ), (y n ) A

x n , y n = c (x n ) (y n ) c lim (f (x n ))

=

lim (f (y n ))

1

lim x0 x

f (x) = 0 x n

1

1

n (f (x n )) =

1/n = (n) = (1, 2, 3, · · · )

1

(x n ) x n :=

x = 0

(x) :

=

  +1

0

  1

x > 0,

x = 0,

x < 0.

lim x0 (x)

(x n ) (y n ) x n :=

y n := n

0 0 ( (x n )) = n = (1) = (1, 1, · · · ) 1

1

n

1

1

( (y n )) = (n ) = (1) = (1, 1, · · · ) 1

1

(x) =

x n

x

|x|

x

=

(1) n

n

:=

(x n ) 0 x n

=

0

(1) n

n

= (1) n = (1, +1, 1, · · · )

0

( (x n )) =

lim sin x

f (x) = sin x , x

1

1

= 0. (x n ) (y n )

x n :=

nπ , y n := (π/2+2πn)

1

1

(f(x n ))

=

(sin ) = (1, 1, · · · ) 1

(f(y n ))

=

(sin (π/2 + 2πn)) = (0, 0, · · · ) 0

1

f (x) = sin x f [1, 1] x 0 f (x)

1

1 0
1 0
1 0
1 0
1 0
1 0
1 0
0
0
0
0
0

0

0

0.8

0.6

0.4

0.2

−0.2

−0.4

−0.6

−0.8

−1

−0.4

−0.3

−0.2

−0.1

0

0.1

0.2

0.3

0.4

f (x) = sin(1/x)

f

f c

(x n ) A c (f (x n )) f (c)

c lim xc f (x) = f (c)

f

:

A −→

R

c

A

L := f (c)

f c (x n ) A (x n ) c (f (x n )) f (c)

ϕ(x) := 1/x 0 ϕ(0) 0

s(x) := (x) 0 lim x0 s(x)

R

f (x) :=

1

x

0

x

f

c f c c

(x n ) c lim(x n ) = c

(f (x n )) = (0, 0, 0, · · · ) lim (f (x n )) = 0

= f (c) = 1

c (y n )

c

lim (f (x n )) = 1

= f (c) = 0 f c c R

f : A −→ R c R A f c V δ (c) M > 0 |f (x)| ≤ M x A V δ (c)

f : A −→ R c R f c

L := lim xc f (x) = 1

|f (x) L| < 1

x = c |f (x)| = |f (c)|

|f (x)| ≤ M

δ > 0 x A 0 < |x c| < δ

|f (x)| < |L| + 1

M := sup {|f (c)|, |L| + 1}

x A V δ (c)

(f + g) (x) :=

f (x) + g(x), (fg) (x) := f (x)g(x), (αf ) (x) := αf (x), f h (x) := f(x) h(x)

h(x)

f, g : A −→ R c R A f g c lim xc f (x) = F lim xc g(x) = G

= 0 x

lim xc (αf ) (x) = αF α

lim xc (f ± g) (x) = F ± G

lim xc (fg) (x) = FG

lim xc f (x) = F

g

G G

= 0 g(x)

= 0 x

(x n ) A x n = c lim(x n ) = c

lim (f (x n )) = F,

lim (g(x n )) = G.

lim ((f ± g) (x n ))

=

lim (f (x n ) ± g(x n ))

=

lim (f (x n )) ± lim (g(x n ))

=

F ± G.

lim xc (f ± g) (x) = F ± G

f 1 , f 2 , ··· , f n lim xc f k (x) = F k

xc (f 1 f 2 ··· f n ) (x) = xc f 1 (x) xc f k (x) ··· xc f n (x) = F 1 F 2 ··· F n .

lim

lim

lim

lim

f 1 = f 2 = ··· = f n := f

xc (f (x)) n = xc f(x) n = F n .

lim

lim

p R, p(x) = a n x n + a n1 x n1 + ··· + a 1 x + a 0

xc p(x) = a n c n + a n1 c n1 + ··· + a 1 c + a 0 = p(c).

lim

p(x) q(x) q(c)

= 0

lim

xc

p(x)

q(x)

= p(c)

q(c) .

f (x)

f

: A −→ R

c R A

x A x

= 0 lim xc f (x)

a f (x) b

a lim

xc f (x) b.

(x n ) A x n

c

lim (f (x n )) = lim xc f (x) a f (x n ) b n N

a lim xc (f(x n )) b a lim xc (f (x)) b

=

c lim(x n ) =

f, g, h : A −→ R c R A

f(x) g(x) h(x)

x A, x

= c lim xc f (x) = L = lim xc h(x) lim xc g(x) = L

(x n ) A x n = c lim(x n ) = c

f(x n ) g(x n ) h(x n ).

(f (x n )) , (g(x n )) (h(x n ))

lim (g(x n )) = lim (f (x n )) = lim (h(x n )) = L,

lim xc g(x) = L.

x sin x x x 0

1 x 2

2

cos x 1 x 0

x x 3

6

sin x x x 0

lim x0 sin x = 0

lim x0 cos x = 1

lim x0 cos x1

x

lim x0 sin x

1

= 0,

= 1,

x

lim x0 x sin x = 0.

0

lim x0 x = lim x0 x = 0

x

sin x

x x

0 = lim

x0 x lim

x0 sin x lim

x0 x = 0

lim x0 sin x = 0

1 x 2

lim x0 cos x = 1

lim x0 cos x

lim x0 (1 x 2 ) = lim x0 1 = 1

2

2

cos x

1

2

x 2

cos x 1 0,

x 0

x > 0

x < 0

x

2

cos x 1

x

0

0 cos x 1

x

x

2 .

f h

f(x) :

=

x

0

2

x 0

x < 0 ,

h(x) :=

0 x 0

x < 0

x

2

x

= 0

f(x) cos x 1

x

h(x).

lim x0 f (x) = lim x0 h(x) = 0 lim x0 cos x1 = 0

x x 3

x sin x x x 3

sin x x x 0

x

6

6

x 0 x

= 0

1 x 2

6

sin x

x

1.

lim x0 1 x 2 = lim x0 1 = 1 lim x0 sin x = 1. 1 sin z 1

z z =

6

x

x , x

1

= 0

1

1 sin x 1.

x > 0

−|x| = x x sin x x = |x|.

1

x < 0

1

|x| = x x sin x x = −|x|

x R x

= 0

1

−|x| ≤ x sin x ≤ |x|.

1

lim x0 −|x| = lim x0 |x| = 0 lim x0 x sin x = 0.

x sin x sin